Design and Synthesis of Carbamazepine-Alkyne Conjugate as Antidiabetic Agent: Study of Chemical Descriptors (log P and p) - Figueroa-Valverde, Lauro; Diaz-Cedillo, Francisco; Camacho-Luis, Abelardo; Lopez-Ramos, Maria; Garcia-Cervera, Elodia (Asian Journal of Chemistry, 2010)
In this work, the carbamazepine-alkyne derivative [4] was synthesized, using the three components system (carbamazepine [1], benzaldehyde [2] and 1-hexyne [3]) in presence of cupric chloride such as catalyst. Additionally, the antidiabetic activity of 1 and 4 compounds was evaluated in vivo in a diabetic animal model. The structure of 4 was confirmed by spectroscopy and spectrometry data. The 1H NMR spectrum showed, up field shifts at 1.23 ppm corresponding to methyl and 2.10 ppm for methylene involved in the alkyne-fragment. Another signals at 6.72 ppm for proton of azepine-ring and several signals (7.25-7.78 ppm) corresponding to the protons of phenyls groups was found. Another results showed that compound 4 induce antidiabetic activity in comparison with compound 1. To delineate the structural chemical requirements of both compounds 1 and 4 on the antidiabetic activity another parameters such as, the descriptors log P and p were calculated. The results showed an increase in both log P and p values of compound 4 with respect to compound 1. In conclusion, these results indicate that the antidiabetic activity of compound 4 depend on their chemical structure and of the lipophilic contributions of the parent molecule and its substituent.